THE ROLE OF THE RED CELL DISTRIBUTION WIDTH IN CAROTID ARTERY DISEASE - Duarte-Gamas, Luis (2020)
Introduction: Carotid disease affects 3-4% of the general population. The association between systemic low-grade inflammation and atherosclerosis has led to the study of blood biomarkers, such as red blood cell distribution width – coefficient of variation (RDW-CV), and their role in the pathophysiology and prognosis of carotid artery disease. The aim of this study was to review the literature regarding the relevance of RDW-CV in carotid artery disease.  Methods: A Medline search was performed in order to identify publications focused on the physiopathology of RDW-CV and its impact in patients with carotid artery disease. Results: Increased RDW-CV was associated with increased carotid intima-media thickness (CIMT) in several studies. It was associated with plaque presence and progression. One study demonstrated an independent association between all-cause and cardiovascular-related mortality in patients with asymptomatic carotid artery stenosis and increased RDW-CV.  Conclusion: RDW-CV is a widely available, easy to measure, and low-cost marker that seems to be associated with subclinical carotid atherosclerosis. However, further studies are needed in order to determine its clinical relevance in this setting.